Utility of newly developed short‐type double‐balloon endoscopy for endoscopic retrograde cholangiography in postoperative patients. Issue 7 (22nd June 2017) - Shimatani, Masaaki; Tokuhara, Mitsuo; Kato, Kota; Miyamoto, Sachi; Masuda, Masataka; Sakao, Masayuki; Fukata, Norimasa; Miyoshi, Hideaki; Ikeura, Tsukasa; Takaoka, Makoto; Okazaki, Kazuichi
Abstract: Background and Aim: The utility of conventional short‐type double‐balloon endoscopy (DBE) for pancreatobiliary disease in patients with postoperative anatomy had been widely acknowledged and accepted. However, some technical difficulties yet remained. In an attempt to solve these problems, the new short‐type DBE (N‐short DBE) was uniquely designed for therapeutic endoscopic retrograde cholangiography (ERC) in postoperative patients. The aim of this study was to evaluate the usefulness of N‐short DBE for ERC in postoperative patients. Methods: From August 2015 to April 2016, ERC using N‐short DBE (DB‐ERC) was performed in 100 postoperative patients (112 procedures). We retrospectively studied the success rate of reaching the blind end, the median time to reach the blind end, the diagnostic success rate, the therapeutic success rate, the median time to complete ERC‐related interventions, the overall success rate, the median time to complete DB‐ERC, and adverse events. Results: The success rate of reaching the blind end was 99.1%. The median time to reach the blind end was 10 min (interquartile range [IQR], 6–19 min). The diagnostic success rate was 98.2%. The therapeutic success rate was 100%. The median time to complete ERC‐related interventions was 36 min (IQR, 22–62 min). The overall DB‐ERC success rate was 97.3%. The median time to complete DB‐ERC was 54 min (IQR, 37–73 min). The occurrence of adverse events was 2.7%. Conclusions: The N‐short DBE for ERC in postoperative patients is useful and safe. DB‐ERC is promising therapeutic modality in such patients and should be selected as the first‐line policy.